The challenge of predicting optical properties of biomolecules: what can we learn from time-dependent density-functional theory? - Castro, Alberto (2009)
http://www.sciencedirect.com/science/article/B6X19-4V2X6RJ-3/2/1e93da040f6f28c5c62005f2523855af